Juridical Analysis of Market Conduct Method in Corporate Credit Agreement and Supervision of Implementation in Indonesia - Delarosa, Stella (International Journal of Business, Economics, and Social Development, 2025)
One of the biggest economic supports of a country is from credit activities, including corporate credit which is a business relationship to obtain business capital for business. Corporate credit agreements are made with a standard agreement originating from the agreement maker's good faith. In connection with this, the Financial Services Authority has made regulations to provide supervision or known as market conduct. However, when referring to POJK 22/2023, it is found that this regulation is still not specifically regulated, especially for standard corporate credit agreements. This research used conceptual approach. This research found that POJK No. 22/2023 has upheld the principles of transparency, fair treatment, and good faith, ensuring consumer protection and responsible business practices. The regulation focuses on clear communication, standardized agreements, and fair dispute resolution to create a fairer environment, but still needs to be refined. By learning from international best practices and refining the regulations, Indonesia can increase trust, protect consumers, and foster a more sustainable financial system through stakeholder collaboration and better oversight.